Red Flour Beetle Aggregation - Collingham, Logan; Marshall, Jeremy (My University, 2018)
The Red flour beetle feeds on grain which is why it is considered a pest. Understanding their aggregation behavior can help us to find new ways to control them. What we don’t yet know is what makes them group together the way they do, whether it be instinctive or a learned behavior. If the beetles are driven by strain-specific behaviors, then we should see a greater proportion of them aggregate with the same strain, which would mean they follow instinctive behavior. The results showed to be contradictory to the original hypothesis. The beetles seemed to show learned behavior due to them grouping more with beetles from the same starting environment rather than the same strain. These results tell us that we need to consider the environment, not just genetic strains, when trying to develop control strategies.
Keywords: Fall 2018